1988
DOI: 10.1007/bf01790094
|View full text |Cite
|
Sign up to set email alerts
|

The microtubular cytoskeleton and chromosomes of unfertilized human oocytes aged in vitro

Abstract: To detect structural alterations in human oocytes that may give rise to predisposition to aneuploidy, unfertilized human oocytes from an IVF programme were processed for indirect anti-tubulin immunofluorescence. The spindle of oocytes aged for 2 days is rather small, and bi- or multipolar. Chromosomes are no longer aligned at the spindle equator but are scattered all over the degenerating spindle. This implies that human oocytes aged for 2 days may no longer be able to develop into a chromosomally balanced, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(51 citation statements)
references
References 17 publications
5
46
0
Order By: Relevance
“…Several mechanisms have been proposed as being responsible for increasing the risk of these abnormalities with increased maternal age. Hormonal imbalances [125,126], abnormalities in follicular development due to the ageing of the somatic cells surrounding the oocyte [127,128] and impaired perifollicular microcirculation [129] have all been implicated as the possible mechanisms behind the effects of ageing on female fertility.…”
Section: Menopausementioning
confidence: 99%
“…Several mechanisms have been proposed as being responsible for increasing the risk of these abnormalities with increased maternal age. Hormonal imbalances [125,126], abnormalities in follicular development due to the ageing of the somatic cells surrounding the oocyte [127,128] and impaired perifollicular microcirculation [129] have all been implicated as the possible mechanisms behind the effects of ageing on female fertility.…”
Section: Menopausementioning
confidence: 99%
“…49 Other authors 43 stated that unbalanced predivision and nondisjunction did not increase significantly with time in culture, but they found an increase in balanced predivision of chromatids also observed previously. 8 Some studies 52,53 revealed that the spindles of human oocytes were sensitive to prolonged in vitro culture and were morphologically altered. From published results, 54 it is conceivable that oocytes from older individuals could be sensitive to even a short culture time, but the morphological anomalies seen in the meiotic spindle suggest other mechanisms, for example, a suboptimal environment for oocyte maturation.…”
Section: Aneuploidy Ratementioning
confidence: 99%
“…Previous reports indicated the high incidence of spindle abnormality and chromosomal alignment abnormality in the oocytes cultured from 48 to 144 hours post insemination [20]. One study reported that unfertilized oocytes in IVF (18 to 22 hours post insemination) revealed normal morphology in 61% and abnormal morphology in 30%, with 9% showing no spindles [21].…”
Section: Discussionmentioning
confidence: 99%